Improving Public's Knowledge of Cardiovascular Health through Health Education - Risnandar, Mochammad Wisnu; Anna, Anastasia; Mirwanti, Ristina (Universitas Padjadjaran, 2024)
Cardiovascular disease in Indonesia has undergone a vast epidemiological transition in the last three decades, with an increase in the number of deaths and disabilities, resulting in the disease burden and high healthcare costs. Community empowerment strategies through educational and participatory approaches are part of efforts to prevent and control cardiovascular disease. A health education program called